A Descriptive Analysis of Therapeutic Drug Monitoring In India - Khan, Sarah; Uz Zaman, Dr.Tabrez (Asian Journal of Pharmaceutical Research and Development, 2024)
Therapeutic drug monitoring (TDM) has evolved into therapeutic drug management throughout the past three to four decades, becoming a crucial facet of precision medicine. Even though India has one of the fastest-growing economies in the world, TDM is not widely used there. At the moment, it is restricted to a small number of teaching hospitals and academic medical institutes. Other therapeutic domains, such anticancer, antifungal, antibacterial, and antitubercular medications, have shown considerable promise to enhance patient outcomes in Indian settings, aside from immunosuppressive pharmaceuticals. The population of this subcontinent is unique in terms of the importance of TDM due to factors like the higher prevalence of nutritional deficiencies, tropical diseases, the widespread adoption of alternative medicines, unlike pharmacogenomics, and the scarcity of population-specific data on the therapeutic ranges of multiple drugs.TDM has not gotten the interest it merits in India, despite its vast applicability and influence on clinical science. This study aims to present a SWOT (strength, weakness, opportunity, and threats) analysis of TDM in India so that suitable measures for promoting TDM growth can be envisaged. Forming a collaborative group with all the stakeholders—including TDM experts, physicians, and the government—and coming up with a National Action Plan to support TDM are urgent needs. To determine the country's TDM focus areas, nodal TDM facilities should be formed, and pilot programmes should be launched. Capacity development and awareness rising are also important steps towards integrating TDM into traditional clinical practice.